DESIGN AND SIMULATION OF PLASTIC INJECTION MACHINE FOR PET (POLYETHYLENE TEREPHTHALATE) - Adhiyoga Mudjoko; Haris Rudianto (Jurnal Ilmiah Teknologi dan Rekayasa, 2023)
PET (Polyethylene Terephthalate) material is widely used for several industries, especially the electronics industry. This study conducted a design and simulation for the manufacture of cases for smartphones using plastic injection machines for the manufacturing process. On the simulation results, it is found that the filling process, temperature and pressure have similarities, namely the distribution starting from the filling center point to the end of the casing design. Defects in manufacturing results are one of the failures of the production process and in this study, it is very rare to find research results that analyze predictions of defects in the smartphone case manufacturing process. On this simulation, defects were able to be detected in the simulation results of the casing design such as line defects and defects due to air bubbles. This research has succeeded in making an overview of the filling process, temperature, pressure, and early detection of defects in the injection process.